THE BASIC RULES , SHARIAH RULINGS AND USE OF THE MUDORABAH AND MUSHORAKAH CONTRACTS IN ISLAMIC FINANCE (International journal of artificial intelligence, 2025)
This thesis analyzes the essence, application methods, types , shariah rulings and basic rules of Mudarabah (profit-sharing) and Musharakah (profit and loss sharing) contracts which are widely discussed but rarely applied in Islamic finance. The thesis highlights the theoretical advantages of these contracts and their role in the Islamic economy, while exploring the reasons for their limited practical implementation.